Implementação de um plugin de suporte à norma de catalogação bibliográfica RDA no software livre AtoM - Ribeiro, Ronai Savegnago (2019)
Giving access to cultural heritage, whether documentary or not, is one of the guarantees that the records that the human being created and documented will not be forgotten. And one of the ways to allow access is to carry out an archival description, in a systematic way and attending norms and standards suitable for that. In this context, we present the AtoM archival description software, an acronym for Access to Memory, which starts from an open source project and allows the archival community to perform tasks of such descriptions. However, the description of documents or objects is not exclusive to the archival community, but also the area of librarianship, which performs bibliographical description, following its respective norms. Thus, this research aims to implement a plugin for open source AtoM software that supports the RDA bibliographic description standard. The justification for this research is contained in the fact that the AtoM description platform can be used by the librarianship community, just as the RDA standard, which was designed to describe objects from areas other than bibliographic, may be available in the software. As a theoretical reference for this research, references were used to conceptualize the cultural heritage, emphasizing the identification of archival and bibliographic documentary heritage in this context. Also discussed and contextualized the topics of archival description, an analysis referring to the AtoM software and its design structure, and a contextualization of the standard of bibliographic description RDA. This research is applied, descriptive and characterized as a bibliographical research. With this, it was possible to identify the archival and bibliographic document as documentary and cultural heritage, identify the way that AtoM software is implemented and perform an analysis in the theoretical framework of the RDA bibliographic standard. And finally, as a result and product, is a new version of AtoM, supporting the bibliographic description of the RDA standard.